2020
DOI: 10.1111/jcal.12487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of digital storytelling games on high school students' critical thinking skills

Abstract: The present study introduced Ren'py software as a digital storytelling (DST) tool to explore the effective use of digital game design learning in promoting critical thinking among high school students. A sample of 46 high school students enrolled in "Thinking Utopia," an elective course in critical thinking for civics education, was put into groups of 3 to 4 for learning activities towards their collaborative designs of DST games. The course stretched across 9 weeks. Students' performance in critical thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…It was determined that the writing skills of pre-service teachers improved due to writing scripts for digital stories, research, and creative thinking skills were improved due to the research they conducted to discover various things, and problem-solving skills were improved due to solving the problems during the digital story development stages. In an empirical study conducted with interviews, Chen and Chuang (2020) revealed that the digital story game encouraged students to improve their critical and problem-solving skills, and media literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that the writing skills of pre-service teachers improved due to writing scripts for digital stories, research, and creative thinking skills were improved due to the research they conducted to discover various things, and problem-solving skills were improved due to solving the problems during the digital story development stages. In an empirical study conducted with interviews, Chen and Chuang (2020) revealed that the digital story game encouraged students to improve their critical and problem-solving skills, and media literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that digital story development provided a strong foundation for the development of 21st-century literacy, or 21st-century skills. It was evidenced in previous studies that DS contributed to the development of digital, global, technological, visual, and knowledge literacy (Brown et al, 2005;Çetin, 2021), critical thinking and problem-solving skills (Chen & Chuang, 2020;Yang & Wu, 2012;McLellan & Wyatt, 2006), reflective thinking skills (Kim & Silver, 2016;Pieterse, 2018;Saritepeci, 2017), communication skills (Karakoyun & Kuzu, 2017;Mnisi, 2015;Al-Amri, 2020;Öztürk & Tunç Ayvaz, 2017), creativity and critical thinking (Anggeraini, 2020;Tabieh et al, 2021), research skills (Çiçek, 2018), and integration skills (Göçen Kabaran et al, 2019). DS has been globally popular as studies demonstrated that it contributed to the development of advanced skills.…”
Section: Introductionmentioning
confidence: 89%
“…The strategies used to teach critical thinking skills include higher order questioning, cooperative learning, enrichment, modeling, real-life applications, and fostering affective domains. The strategies used include higher order questioning in the form of critical thinking questions, active learning by making students learn active independently, and enrichment by exposing students to problem solving in quizzes, materials and understanding the material with audiovisual and transfer processes through animation in Game (Chen & Chuang, 2021;Wardani et al, 2017). Educational games make students more comfortable actively participating in learning because they are already familiar with the graphical environment in using computers.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, integrating the CL technique into the DST activity is a valid way to achieve the benefits of CL mentioned above. Applying collaborative activities during the process of creating DST could contribute to the progress of communication and problem‐solving skills (Chen & Chuang, 2020), and it could be a useful tool to enhance the progress of collaborative writing, which is also a productive skill (Rahimi & Yadollahi, 2017). Furthermore, the combination of cooperative technology and storytelling is considered to assist promoting balanced social cognitive development and the improvement of narrative and social interaction skills (Cassell & Ryokai, 2001; Decortis & Rizzo, 2002; Di Blas et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%